2019
DOI: 10.1371/journal.pone.0224274
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics profiles associated with HbA1c levels in patients with type 2 diabetes

Abstract: Glycated hemoglobin (HbA1c) is an indicator of the average blood glucose concentration. Failing to control HbA1c levels can accelerate the development of complications in patients with diabetes. Although metabolite profiles associated with HbA1c level in diabetes patients have been characterized using different platforms, more studies using high-throughput technology will be helpful to identify additional metabolites related to diabetes. Type 2 diabetes (T2D) patients were divided into two groups based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…9 However, a Korean cohort study did not mention 3-HB. 7 Factors that affect 3-HB are unclear. For the untreated patients with MetS in this study, we suggest that the elevated 3-HB is a result of a compensatory response because they have a ketogenic tendency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 However, a Korean cohort study did not mention 3-HB. 7 Factors that affect 3-HB are unclear. For the untreated patients with MetS in this study, we suggest that the elevated 3-HB is a result of a compensatory response because they have a ketogenic tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found higher 3‐HB in the plasma and urine of patients with T2D, including data from a Chinese cohort study 9 . However, a Korean cohort study did not mention 3‐HB 7 . Factors that affect 3‐HB are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolites with significant differences in their concentrations in the different analysis groups were identified. All procedures were performed as described previously [ 16 , 17 ]. Briefly, the serum samples were analyzed using the API 4000 QTRAP LC/MS/MS system (Applied Biosystems, Foster City, CA, USA) and the Agilent 1200 HPLC system (Agilent Technologies, Santa Clara, CA, USA), following the manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In targeted metabolomics, absolute concentrations of a limited number of known metabolites are quantified, giving this method high sensitivity and selectivity [ 10 ]. In T2DM, metabolomics has led to the discovery of several metabolic biomarkers closely related to the occurrence, development and progress of the disease [ 11 ]. Various regulatory pathways, including the regulation of sugar, fat and protein are found to be disturbed in T2DM [ 3 ].…”
Section: Introductionmentioning
confidence: 99%